Detailed assessment of nutritional status and eating patterns in children with gastrointestinal diseases attending an outpatients clinic and contemporary healthy controls - Tsiountsioura, M; Wong, J; Upton, J; McIntyre, K; Dimakou, D; Buchanan, E; Cardigan, T; Flynn, D; Bishop, J; Russell, R; Barclay, A; McGrogan, P; et al. (Springer Nature, 2014)
Background/objectives: In the era of modern multidisciplinary clinical management, very little is known about the prevalence and presentation of malnutrition in children with gastrointestinal disorders (GastroD) particularly employing composite, global measures of nutritional status. Subjects/methods: Anthropometry, body composition, dietary intake, eating habits and grip strength were assessed with bedside methods in 168 patients from outpatient gastroenterology clinics (n, median (IQR) years; Crohn’s disease (CD): n=53, 14.2 (11.6:15.4); ulcerative colitis (UC): n=27, 12.2 (10.7:14.2); coeliac disease: n=31, 9.3 (7.5:13.6); other GastroD: n=57, 9.8 (7.2:13.8)) and compared with 62 contemporary healthy controls (n, median (IQR): 9.8 (6.9:13.8)) and the results of the recent UK, National Diet and Nutritional Survey (NDNS). Results: Children with CD had lower BMI z-scores than controls (median (IQR): −0.3 (−0.9:0.4) vs 0.3 (−0.6:1.4); P=0.02) but only 2% were classified as thin (BMI z-score <−2 s.d.). The prevalence of obesity in children with UC was 19%, 6% in CD, 11% in children with other GastroD and 15% in controls. No difference was found in grip strength measurement between groups. Except for CD children, the proportion of patients with suboptimal micronutrient intake was similar to that of controls and the cohort of children from the latest NDNS. A higher proportion of children with CD had suboptimal intake for riboflavin, vitamin B6 and calcium and consumed significantly more meat products, juices (including carbonated drinks), spreads/jams and crisps and savoury snacks and significantly fewer portions of dairy, fish, fruits and vegetables compared with healthy controls. Conclusions: GastroD affect children’s body composition, growth, strength, dietary intake and eating habits, particularly CD, but to a lesser extent than expected.